KARAKTERISTIK HABITAT DAN WILAYAH JELAJAH BEKANTAN DI HUTAN MANGROVE DESA NIPAH PANJANG KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT - Agus Priyono Kartono; Andri Ginting; Nyoto Santoso (Department of Forest Resources Conservation and Ecotourism - IPB University, 2008)
Proboscis monkey (Nasalis larvatus Wurmb, 1787) is a member of the subfamily Colobinae which is a riverine dwelling, sexually dimorphic species endemic to the island of Borneo in Southeast Asia. This species was protected by Indonesian law No. 5/1990, categorized as vulnerable (A2c) on IUCN Red Data Book 2008, and protected under CITES Appendix I. Characteristics of habitat type occupied by proboscis monkey were dominated by vegetation types as Rhizophora apiculata, R. mucronata, Bruguiera gymnorrhiza and B. parviflora. Length of distance between sites used for daily activity with river bodies was about 158.4±75.4 m. Home range of proboscis monkey on mangrove and riverine forest at Nipah Panjang Village was about 13.4 ha to 38 ha. Daily range of this species was about 904.2±117.1 m/day, maximum radius of daily movement 371.3±46.6 m and night position shift 191.5±65.3 m. Total number of individual in each proboscys monkey group in riverine and mangrove forest on Nipah Panjang Village was 18 ± 5 (=0.05).Keywords: Proboscis monkey, home range, habitat characteristic, groups size, daily range